Parent inheritance, founder expertise, and venture strategy: Determinants of new venture knowledge impact - Basu, Sandip; Sahaym, Arvin; Howard, Michael D.; Boeker, Warren (Journal of Business Venturing, 2015)
A genealogical theory of new venture creation posits that “parent” firm routines are transferred to “progeny” ventures founded by the former employees of these parents. This study examines how the knowledge available to a venture from its parent firms and individual founders, as well as its initial technological direction, influences its own creation of impactful knowledge. We argue that new knowledge creation involves the recombination of underlying knowledge elements and hypothesize that the degree to which the venture's knowledge domain overlaps with the parents' knowledge has positive, but diminishing effects on the impact of knowledge created by the venture. We also predict that the breadth of founders' personal knowledge has a positive effect, but that the divergence between individual founders' and parent firm's knowledge domains has a negative effect on the creation of impactful knowledge by the venture. We test our predictions using a sample of 219 biotechnology ventures founded over the eleven year period 1990–2000 and tracked through 2010. Our results contribute to the entrepreneurship, knowledge creation, and genealogical literatures.